2021
DOI: 10.3153/fh21020
|View full text |Cite
|
Sign up to set email alerts
|

Determination of some minerals and heavy metal levels in Urfa cheese and cow's milk

Abstract: This research was carried out to determine the levels of some minerals and heavy metals in Urfa cheeses and cow's milk offered for sale in Şanlıurfa. Mineral and heavy metal levels were determined by analysing 18 Urfa cheese and 21 cow milk samples collected from retail outlets with ICP-MS. Mean mineral and heavy metal contents in Urfa cheese samples were; magnesium (Mg) 129.8 ±31.14 mg/kg, calcium (Ca) 2712.66 ±1002.4 mg/kg, potassium (K) 272.06 ±127.21 mg/kg, titanium (Ti) 7.48 ±2.63 mg/kg, zinc (Zn) 40.4 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…For this reason, the determination of the heavy metal level in cheeses is very important [ 24 ]. As for the heavy metal concentration in this study, their content was very low, comparable to values reported in the literature [ 24 , 25 , 26 , 27 ]. Lead was below the permissible levels.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For this reason, the determination of the heavy metal level in cheeses is very important [ 24 ]. As for the heavy metal concentration in this study, their content was very low, comparable to values reported in the literature [ 24 , 25 , 26 , 27 ]. Lead was below the permissible levels.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, low levels of cadmium, below 0.008 ppm, were detected. This is, nevertheless, important due to the high toxicity presented by cadmium [ 26 ]. Our study demonstrated a concentration of cadmium similar to the level obtained by Al Sidawi et al The most often indicated source of cheese contamination with toxic metals by these authors is residues of these metals in animal fodder and in water [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, heavy metal contamination is infected from environmental sources such as soil and water or feed consumed by animals. In addition, metals in the composition of machinery and equipment used during milk storage and processing may leach into the product during milking [6].…”
Section: Introductionmentioning
confidence: 99%